Designing Electronic Kanban Using Conwip Method To Reduce Delays On Pylon Assembly Line In Pt. Dirgantara Indonesia - Sarah Ayutami; Dida Diah Damajanti; Widia Juliani (eProceedings of Engineering, 2019)
Abstract— PT. Dirgantara Indonesia is a company engaged in the manufacture of aircraft. Today, companies face problems to meet demand in a timely manner. The problem occurs because of the lack of parts needed to assemble the required components. This happens due to the delay in getting information about the parts needed and there is no warning about the availability of the parts needed, it makes some parts are not available in store. The lack of the parts and component from the required process causes the assembly line stop running. So that tail boom assembly process will also be delayed. The Incorrect item arrival schedule and unsuitable quantities are a major problem in the airbus tailboom assembly line. To obtain all the components and subassembly that are needed in the right amount and at the right time, this idea of this study is designing the electronic Kanban system which consists of calculating Kanban cards, design the mechanism for using the Kanban System, design the application of Electronic Kanban System and the number of buffer stock so that the required part is available in store. The results of this study are the number of Kanban card which have a number of buffer stocks to control the flow of item required and Electronic Kanban Systems to show the report of actual working status in the assembly line and classify the required information in a card.